CHINESE FACTOR IN RUSSIAN-AMERICAN RELATIONS - M. А. Troitskiy (Сравнительная политика)
The article claims that despite growing cooperation between Russian and China on the one hand and increasing interdependence between China and the U.S. on the other, Russian-American dialogue on China is absent not only in official discussions, but also in expert debates. Although Russian partnership with China is not free of disagreements on certain issues, Moscow believes that it is crucial for its international strategy and retains deep trust in Beijing benevolent behavior. The U.S., however, are much less confident in their strategy towards China.